2019
DOI: 10.1109/jstqe.2018.2854539
|View full text |Cite
|
Sign up to set email alerts
|

The Photobiomodulation of Vital Parameters of the Cancer Cell Culture by Low Dose of Near-IR Laser Irradiation

Abstract: The mechanisms underlining the cell adaptive and/or activating oxidative stress called low level light (LLLT) or photobiomodulation therapies (PBMT) still remain unclear for near-infrared (NIR) spectrum range (750-3000 nm) especially for 1265-1270 nm range (highest absorption by molecular oxygen). It is most probably that the mitochondria may also appear to be the main target for these wavelengths. It is known that mitochondria can generate ROS under visible and 800-1060 nm spectrum range irradiation which in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
0
19
0
2
Order By: Relevance
“…15,19 Interestingly, recent studies demonstrated that a brief exposure of the skin with NIR laser ranging from 1061 to 1301 nm at an irradiance of 0.5 to 5 W∕cm 2 augmented the immune response to intradermal vaccination and conferred protection. [20][21][22][23][24][25] In these studies, the activation of innate responses, subsequent migration of skinresident dendritic cells, and augmentation of adaptive response were dependent on the generation of ROS. 21 It has also been reported that broadband NIR light (760 to 1440 nm) induces the formation of mitochondria-derived ROS and subsequent increase in redox potential in cultured human dermal fibroblasts.…”
Section: Introductionmentioning
confidence: 93%
“…15,19 Interestingly, recent studies demonstrated that a brief exposure of the skin with NIR laser ranging from 1061 to 1301 nm at an irradiance of 0.5 to 5 W∕cm 2 augmented the immune response to intradermal vaccination and conferred protection. [20][21][22][23][24][25] In these studies, the activation of innate responses, subsequent migration of skinresident dendritic cells, and augmentation of adaptive response were dependent on the generation of ROS. 21 It has also been reported that broadband NIR light (760 to 1440 nm) induces the formation of mitochondria-derived ROS and subsequent increase in redox potential in cultured human dermal fibroblasts.…”
Section: Introductionmentioning
confidence: 93%
“…Параметры лазерного излучения. В качестве источника низкоинтенсивного лазерного излучения мы использовали полупроводниковый узкополосный (высококогерентный) лазер с шириной линии излучения ~ 0,001 нм (Yenista Optics, OSICS T100 Tunable Laser Module T100 1310) [14].…”
Section: материалы и методы исследованияunclassified
“…Nowadays laser therapy is widely used in dentistry [7,8], photodynamic therapy [9,10], skindisease and cosmetic defects treatment [11,12] with the use of photosensitizers and without their use. It is known that the various range of wavelength can cause diametrically opposite cellular effects from damage [13,14] up to regeneration [15,16], which have great perspectives both for treatment and rehabilitation after it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest resonance absorption band of oxygen is in the range of 1265-1270 nm, where no absorption of known chromophores occurs in the living cell. The light-oxygen effect (1265-1270 nm ranges) can activate or damage (depending on the energy density) the biosystems through a direct photoexcitation of molecular triplet oxygen into the singlet oxygen [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%